Mycophenolic acid in Rheumatology: mechanisms of action and severe adverse events - G.F. Ferraccioli; M. De Santis; G. Zizzo (PAGEPress Publications, 2011)
MPA is clinically administered as morfolinoethyl ester (mycophenolate mofetil, MMF) or, more recently, as a salt (enteric-coated mycophenolate sodium). It is a fermentation product of Penicillium brevicompactum and other analogue fungi, identified by Gosio in 1893 as a weak antibacterial agent; in 1969 Franklin and Cook discovered its capacity to inhibit the inosine mono phosphate dehydrogenase (IMPDH), an enzyme involved in purine nucleotide synthesis (1)...